2013
DOI: 10.3892/mmr.2013.1565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary guidance on the symptoms, quality of life and habitual dietary intake of patients with irritable bowel syndrome

Abstract: Abstract. Diet is important in triggering the symptoms of irritable bowel syndrome (IBS). This study investigated the impact of dietary guidance on the symptoms, quality of life and habitual diet of patients with IBS. Forty-six patients who included. Of these patients, 17 completed the entire study. Each patient attended three sessions (~45 min in duration) and received individual guidance on their dietary management. The patients were asked to complete the following questionnaires prior to receiving the dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 32 publications
10
93
1
3
Order By: Relevance
“…(24,33,38) Meta-analysis data (37) reported a significant improvement in the IBS-QOL score (OR 1.84, 95% CI 1.12-3.03; I 2 = 0.00, p = 0.39).…”
Section: Lfd Improves Satisfaction With Symptom Control and Qolmentioning
confidence: 99%
See 2 more Smart Citations
“…(24,33,38) Meta-analysis data (37) reported a significant improvement in the IBS-QOL score (OR 1.84, 95% CI 1.12-3.03; I 2 = 0.00, p = 0.39).…”
Section: Lfd Improves Satisfaction With Symptom Control and Qolmentioning
confidence: 99%
“…Previous studies have established the importance of offering education, information and general support in the management of IBS. Given individually or to a group, (38,45) advice and guidance on FODMAP restriction is a cost-effective therapy in the management of IBS-related bloating. Nevertheless, the ideal mode and medium for patient education remain debatable.…”
Section: Differential Effect Of Fodmap Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have since reported on the mechanisms underlying the impact of FODMAPs on intestinal function, and the therapeutic role that a low FODMAP diet may play for patients with IBS-related gastrointestinal symptoms [18,[31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Malabsorption of fructose or lactose and small intestinal bacterial overgrowth were combined in 75.6%, 37.8%, and 13.3% of patients, respectively; fructose malabsorption was significantly associated with symptom reduction subsequent to following a low FODMAP diet [37] . Other prospective studies have demonstrated the beneficial effects of FODMAP-related dietary guidance [38] and intervention [39] on overall IBS symptoms and quality of life. A nonrandomized controlled trial conducted in England compared IBS patients who followed a low FODMAP diet with those who received standard dietary advice [40] .…”
Section: Introductionmentioning
confidence: 99%